Conductive binder and preparation method thereof, negative plate and battery

By using block copolymers and phenolic hydroxy organic compounds to coat carbon material, the mechanical stress and conductive network damage caused by volume changes in silicon-based anode materials in lithium batteries are solved, and higher battery cycle stability and electrochemical performance are achieved.

CN119752369APending Publication Date: 2025-04-04JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980899.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In existing lithium batteries, the mechanical stress and conductive network damage caused by volume changes during the charge and discharge cycle limit the cycle stability and electrochemical performance of the battery.

Method used

A conductive adhesive composed of block copolymers and a carbon material coated with phenolic hydroxy organic compounds is used to form a physical crosslinking network through hydrogen bonding between flexible segments and polyacrylic segments to enhance the mechanical properties and electrical conductivity of the material.

Benefits of technology

The tensile, elastic and electrical conductivity of the conductive adhesive are improved, the structural stability and conductive network integrity of the silicon-based material in the charge and discharge cycle are maintained, and the cycle stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222308070000021
    Figure BDA0005222308070000021
  • Figure BDA0005222308070000031
    Figure BDA0005222308070000031
  • Figure BDA0005222308070000081
    Figure BDA0005222308070000081
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a conductive binder and a preparation method thereof, a negative plate and a battery. The conductive adhesive comprises a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound, the block copolymer comprises a polyacrylic acid chain segment and a flexible chain segment; the flexible chain segment comprises an acrylate polymer containing an ether oxygen group. The preparation method of the conductive binder comprises the following steps: carrying out first mixing on a carbon material and water, adjusting the pH value, then adding a phenolic hydroxyl organic compound, and carrying out second mixing to obtain a carbon material coated with the phenolic hydroxyl organic compound; acrylic acid, an acrylate organic matter containing an ether oxygen group, a carbon material coated with a phenolic hydroxyl organic compound, an initiator and a solvent are mixed and subjected to a polymerization reaction, and the conductive adhesive is obtained. The structural stability of the negative electrode active material and the integrity of a conductive network can be maintained, so that the capacity retention ratio of the negative electrode active material in the charge-discharge process is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a conductive adhesive and a preparation method thereof, a negative electrode sheet and a battery. Background Art

[0002] With the widespread application of lithium batteries in new energy vehicles, energy storage and other fields, the development of lithium-ion batteries with higher energy density and longer cycle life has always been a hot topic of research. Among the negative electrode materials of lithium batteries, the theoretical specific capacity of silicon is as high as 4200mAh / g, which is almost 10 times that of graphite, making it one of the most promising negative electrode materials for the new generation of lithium-ion batteries. However, the volume expansion of silicon particles caused by repeated lithium ion insertion and extraction triggers problems such as material crushing, electrical contact failure and unstable SEI layer, which seriously limits the electrochemical performance of silicon-based negative electrodes. In batteries, binders are very important for maintaining the mechanical integrity and conductive network integrity of electrodes. Suitable binders can effectively improve the electrochemical performance of silicon negative electrodes. However, due to weak intermolecular forces and brittleness, traditional polyvinylidene fluoride (PVDF) and carboxymethyl cellulose (CMC) are not suitable for silicon-based negative electrodes. Polyacrylic acid (PAA) is a water-soluble polymer containing a large number of carboxyl groups, which can produce strong hydrogen bonds with silicon particles. It has been proven in practice to be an ideal binder for silicon-based negative electrode materials.

[0003] However, the chain rigidity and relatively high glass transition temperature of PAA homopolymer limit the elasticity of amorphous PAA, which is brittle at room temperature and has poor stretchability, so it cannot adapt to the huge volume changes of silicon during the charge / discharge cycle for a long time. And because silicon is a semiconductor, the electron / ion transmission between silicon particles is slow. When preparing silicon negative electrodes, conductive agents are required to ensure high conductivity. When repeated large volume changes occur, the conductive network between the active material and the conductive agent is easily destroyed, resulting in rapid capacity decay. Summary of the invention

[0004] In view of this, the present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a conductive binder and a preparation method thereof, a negative electrode sheet and a battery, which can alleviate the problem that the existing binder PAA homopolymer has poor stretchability, which causes it to be unable to adapt to the volume change of the negative electrode active material during the charge / discharge process of the lithium battery, and the conductive grid between the negative electrode active material and the conductive agent is destroyed due to repeated volume changes. The conductive binder can improve its stretchability, elasticity and conductivity, which is beneficial to maintaining the structural stability and conductive network integrity of the silicon-based material during the charge and discharge cycle, and thus helps to improve the cycle stability of the battery.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] According to a first aspect of the present application, the present application provides a conductive adhesive, which includes a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound;

[0007] The block copolymer comprises a polyacrylic acid segment and a soft segment;

[0008] The soft segment comprises an acrylic polymer containing an ether group.

[0009] In any embodiment, based on the total mass of the block copolymer, the mass proportion of the soft segment is 2% to 10%.

[0010] In any embodiment, the mass ratio of the block copolymer to the carbon material coated with the phenolic hydroxyl organic compound is 1:(0.02-0.05).

[0011] In any embodiment, the block copolymer and the carbon material coated with the phenolic hydroxyl organic compound are blended to form a three-dimensional network structure.

[0012] In any embodiment, the phenolic hydroxy organic compound comprises tannic acid.

[0013] In any embodiment, the carbon material includes at least one of carbon nanotubes or graphene.

[0014] In any embodiment, the carbon nanotubes include at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0015] In any embodiment, the diameter of the carbon nanotube is 1 nm to 10 nm, and the length of the carbon nanotube is 5 μm to 50 μm.

[0016] In any embodiment, the block copolymer has a number average molecular weight of 1,000 to 100,000.

[0017] In any embodiment, the structural formula of the acrylic ester polymer containing ether group is as follows:

[0018]

[0019] Here, m and n are independently integers from 1 to 5, and b is an integer greater than 0.

[0020] In any embodiment, the structural formula of the acrylic ester polymer containing ether radicals is selected from or At least one of .

[0021] A second aspect of the present application provides a method for preparing a conductive adhesive, the method comprising the following steps:

[0022] The carbon material and water are first mixed, the pH value is adjusted, and then a phenolic hydroxyl organic compound is added for second mixing to obtain a carbon material coated with the phenolic hydroxyl organic compound;

[0023] Acrylic acid, acrylate organic matter containing ether radical, carbon material coated with phenolic hydroxyl organic compound, initiator and solvent are mixed and polymerized to obtain conductive adhesive.

[0024] In any embodiment, the mass ratio of the carbon material to water is 1:(50-300).

[0025] In any embodiment, the target pH value is 8-9.

[0026] In any embodiment, the mass ratio of the phenolic hydroxyl organic compound to the carbon material is (0.1-0.3):1.

[0027] In any embodiment, the first mixing time is 3 hours to 6 hours.

[0028] In any embodiment, the second mixing time is 2 hours to 5 hours.

[0029] In any embodiment, the structure of the acrylate organic compound containing an ether group is:

[0030]

[0031] Here, m and n are independently integers ranging from 1 to 5.

[0032] In any embodiment, the ether-oxygen-containing acrylic ester organic compound includes at least one of 2-methoxyethyl 2-acrylate or ethoxyethoxyethyl acrylate.

[0033] In any embodiment, the mass ratio of the acrylic acid to the solvent is 1:(18-50).

[0034] In any embodiment, the solvent includes at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone, methanol or ethanol.

[0035] In any embodiment, the mass ratio of the acrylic acid to the ether-oxy group-containing acrylic ester organic matter is 1:(0.02-0.1).

[0036] In any embodiment, the mass ratio of the acrylic acid to the carbon material coated with the phenolic hydroxyl organic compound is 1:(0.02 to 0.1).

[0037] In any embodiment, the mass ratio of the acrylic acid to the initiator is 1:(0.1-0.2).

[0038] In any embodiment, the initiator includes at least one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide.

[0039] In any embodiment, the polymerization reaction temperature is 60° C. to 90° C., and the polymerization reaction time is 12 h to 24 h.

[0040] In any embodiment, after the polymerization reaction is completed, post-treatment is further included to obtain a conductive adhesive.

[0041] In any embodiment, the post-treatment comprises: placing the product obtained after the polymerization reaction in liquid nitrogen for quenching, then centrifuging, washing and freeze-drying.

[0042] In any embodiment, the freeze-drying temperature is -45°C to -55°C, and the freeze-drying time is 12h to 24h.

[0043] The third aspect of the present application provides a negative electrode sheet, which includes a negative electrode active material and the conductive binder described above or the conductive binder prepared by the method described above.

[0044] In any embodiment, the mass of the conductive binder is 2% to 5% of the negative electrode active material.

[0045] In any embodiment, the negative electrode active material includes a silicon-carbon composite material.

[0046] In any embodiment, the surface density of the negative electrode sheet is 7 to 15 mg / cm 2 .

[0047] A fourth aspect of the present application provides a battery, comprising the above-mentioned conductive adhesive, or the conductive adhesive prepared by the above-mentioned method, or the above-mentioned negative electrode sheet.

[0048] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0049] In the embodiment of the present application, the provided conductive binder and its preparation method are mainly composed of a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound, wherein the block copolymer includes a polyacrylic acid segment and a flexible segment, and the flexible segment includes an acrylate polymer containing an ether group. In this way, the introduction of the acrylate polymer containing an ether group in the flexible segment can improve the flexibility of the conductive binder. At the same time, the acrylate polymer containing an ether group and the polyacrylic acid segment can form a physical cross-linking network through hydrogen bonding, improve the mechanical properties of the material, and maintain the structural integrity of the negative electrode active material during the charge and discharge cycle during the cycle process; and the introduction of the carbon material coated with a phenolic hydroxyl organic compound can ensure the continuity of the conductive network of the negative electrode active material during the charge and discharge cycle, and ensure the capacity retention rate of the negative electrode active material during the charge and discharge process, so that the cycle stability of the battery using the conductive binder can be improved.

[0050] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0051] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] Generally, a battery includes an electrode assembly and an electrolyte, and the electrode assembly includes a diaphragm, a positive electrode sheet and a negative electrode sheet. Silicon has become one of the most promising negative electrode active materials due to its high theoretical specific capacity. However, silicon will expand in volume during the battery charging and discharging process, resulting in material crushing, electrical contact failure, and SEI layer instability, which seriously affects the electrochemical performance of silicon-based negative electrodes. Binders can maintain the mechanical integrity and conductive grid integrity of negative electrode materials. Therefore, suitable binders can effectively improve the electrochemical performance of silicon negative electrodes. In the related art, the binder used in silicon negative electrodes is mainly polyacrylic acid (PAA). However, in the existing process, polyacrylic acid homopolymer is a rigid segment (the structure of the rigid segment is relatively fixed and does not have the ability to expand or shorten), and its glass transition temperature (about 102°C) is high (the glass transition temperature is the temperature corresponding to the transition of the polymer from the glassy state to the highly elastic state; the greater the rigidity of the molecular chain, the higher the glass transition temperature), making it brittle and poorly tensile at room temperature. Therefore, it cannot adapt to the volume change of silicon-based negative electrode materials during the charge and discharge cycle. At the same time, when silicon-based negative electrode materials undergo repeated volume changes, they will also cause damage to the conductive grid between the active material and the conductive agent.

[0058] In view of this, the embodiment of the present application provides a conductive binder and a preparation method thereof, which can be used in a negative electrode sheet, especially in a negative electrode sheet containing a silicon-based material, in order to alleviate the shortcomings of the existing binder PAA homopolymer, and has better stretchability, elasticity and conductivity, and further provides a negative electrode sheet and a battery containing the conductive binder on this basis. The present application and optional embodiments are described in more detail below.

[0059] [Conductive adhesive]

[0060] In some embodiments, the present application provides a conductive adhesive, which includes a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound;

[0061] The block copolymer includes a polyacrylic acid segment and a flexible segment; the flexible segment includes an acrylic acid ester polymer containing an ether group.

[0062] The conductive adhesive of the present invention has excellent stretchability and elasticity, and can ensure the continuity of the conductive network in the electrode, thereby alleviating the above-mentioned problems existing in the prior art. In detail:

[0063] The conductive adhesive of the present invention is mainly composed of a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound, wherein the block copolymer segment includes a polyacrylic acid segment and a flexible segment, and the flexible segment includes an acrylate polymer containing an ether group. Thus, by making the flexible segment include an acrylate polymer containing an ether group, on the one hand, it has a lower glass transition temperature, and then the flexibility of the conductive adhesive can be improved, so that the conductive adhesive becomes relatively soft, so that it has better stretchability and elasticity, can withstand greater deformation, and can effectively buffer the mechanical stress caused by volume change of the negative electrode active material during the charge and discharge process; on the other hand, the ether oxygen bond in the acrylate polymer containing an ether group can be used as a hydrogen bond receptor, and the carboxyl group in polyacrylic acid is a hydrogen bond donor, so the acrylate polymer containing an ether group in the flexible segment and the polyacrylic acid segment can form a physical cross-linked network through hydrogen bonding, which can reduce the irreversible slip of the block copolymer, improve the mechanical properties of the material, and maintain the structural integrity of the negative electrode active material during the charge and discharge cycle during the cycle process. In addition, the provided conductive binder also contains a carbon material coated with a phenolic hydroxyl organic compound, wherein the introduction of the carbon material can give the binder a certain conductivity. The conductive binder can serve as a bridge for electronic connection between particles, promote the migration of charge carriers between negative electrode active materials such as silicon particles, and enable the conductive network of the negative electrode active material to maintain continuity after multiple cycles.

[0064] Therefore, compared with the currently rigid PAA homopolymer, the conductive binder provided by the present invention can make the binder relatively soft by introducing flexible segments, has better stretchability and elasticity, can withstand greater deformation than PAA, and can effectively buffer the mechanical stress generated by the volume change of silicon materials during the charge and discharge process, thereby facilitating the maintenance of the structural stability of silicon-based negative electrode materials during the charge and discharge cycle. At the same time, the introduction of carbon materials into the conductive binder can ensure the continuity of the conductive network during the cycle process, thereby facilitating the improvement of the cycle stability of the battery.

[0065] It can be understood that the conductive adhesive provided by the present application can be used in negative electrode sheets, especially in negative electrode sheets including silicon-based materials as active materials, which is more preferred, and can alleviate the problems of poor elasticity and stretchability of existing adhesives. Of course, in addition to this, the conductive adhesive can also be used in other structures or scenarios, providing conductive adhesion to any scenario or layered structure with similar requirements. The embodiments of the present application do not specifically limit the specific use scenarios and working conditions of the adhesive.

[0066] In the present application, the term "binder" generally refers to a chemical compound, polymer or mixture that forms a colloidal solution or colloidal dispersion in a dispersion medium; it can also refer to a colloidal solution or colloidal dispersion formed by a polymer in a dispersion medium.

[0067] The adhesive provided in the present application is a conductive adhesive. Compared with conventional adhesives, the conductive adhesive not only has certain adhesiveness, but also has certain conductivity due to the introduction of carbon materials, so it is called a conductive adhesive.

[0068] In this application, the term "block copolymer" mainly refers to a special polymer prepared by linking two or more polymer segments with different properties. Block copolymers with specific structures will show different properties from simple linear polymers, many random copolymers and even mixtures of homopolymers. Common block copolymers are AB type and ABA type, in which A and B are long chain segments; there are also (AB)n type multi-segment copolymers, in which A and B segments are relatively short.

[0069] In the present application, the block copolymer is a block copolymer with an AB structure, or a block copolymer with an ABA structure, that is, it can be an AB type block copolymer or an ABA type block copolymer. Among them, the AB type block copolymer refers to a two-block copolymer with an A-block on one side and a B-block on the other side; the ABA type block copolymer refers to a triblock copolymer with A-blocks on both sides and a B-block in the middle. The A-block and the B-block can be polymer segments with a predetermined molecular weight formed by polymerization of different monomers. In some embodiments, the A-block is a polyacrylic acid segment formed by polymerization of acrylic acid, and the B-block is an ether-oxygen-containing acrylic acid ester polymer segment formed by polymerization of acrylic acid ester monomers, or the B-block is a polyacrylic acid segment formed by polymerization of acrylic acid, and the A-block is an ether-oxygen-containing acrylic acid ester polymer segment formed by polymerization of acrylic acid ester monomers. The A-block and the B-block can be covalently bonded in an orderly manner to form an AB type or ABA type block copolymer.

[0070] In this application, the term "polyacrylic acid segment" refers to a is an integer greater than 0. Its glass transition temperature is not less than 80° C. Therefore, the polyacrylic acid segment has a high elastic modulus, a relatively fixed structure, and has no ability to expand or shorten, and is a rigid segment.

[0071] In the present application, the term "flexible segment" refers to a polymer having a glass transition temperature of no more than 10°C. The glass transition temperature of the flexible segment is relatively low, and therefore, the flexible polymer is in a highly elastic state at room temperature. The segments of the flexible polymer can move, and the flexibility can be increased by means of the segment movement of the flexible polymer, thereby expanding the free volume of the segment movement.

[0072] By grafting an acrylate polymer containing ether groups in a flexible segment onto polyacrylic acid in a rigid segment, the high viscosity and brittleness of polyacrylic acid can be improved, its glass transition temperature can be lowered, the stretchability and elasticity of the conductive binder can be increased, the brittleness of the binder can be reduced, it can withstand greater deformation, and can effectively buffer the mechanical stress generated by the volume change of the negative electrode active material during the charge and discharge process.

[0073] In this application, the term "etheroxy" refers to The groups, R, R' are each independently selected from hydrocarbon groups.

[0074] In the present application, the term "acrylate" refers to a general term for esters of acrylic acid and its homologues.

[0075] In the present application, the term "polymer" includes, on the one hand, a collection of macromolecules that are chemically uniform but differ in degree of polymerization, molar mass and chain length, prepared by polymerization. The term also includes, on the other hand, derivatives of such a collection of macromolecules formed by polymerization, i.e. compounds that can be obtained by reaction, for example addition or substitution, of functional groups in the above-mentioned macromolecules and can be chemically uniform or chemically heterogeneous.

[0076] By selecting ether-group-containing acrylic polymers as flexible chain segments, not only can the flexibility of the conductive binder be improved, the stretchability and elasticity of the conductive binder be increased, but the mechanical stress generated by the volume change of the negative electrode active material during the charge and discharge process can be effectively buffered; the ether-group can act as a hydrogen bond acceptor, and the carboxyl group in acrylic acid is a hydrogen bond donor. The two form a physical cross-linking network through hydrogen bonding, reduce the irreversible slipperiness of the block copolymer, and improve the mechanical properties of the material. It can effectively inhibit or alleviate the expansion of the active material during the charge and discharge process and maintain the structural integrity of the electrode material.

[0077] In some specific embodiments, the structural formula of the acrylic acid ester polymer containing ether group is as follows:

[0078]

[0079] Wherein, m and n are independently integers in the range of 1 to 5, and b is an integer greater than 0. That is, m can be an integer of 1, 2, 3, 4 or 5, and n can be an integer of 1, 2, 3, 4 or 5. The values ​​of m and n can be the same or different, and b can be greater than 1, 10, 50, 100, 200 or 500, etc.

[0080] Optionally, in some embodiments, the structural formula of the ether-oxy group-containing acrylic polymer can be selected from or Any one or both of .

[0081] Of course, in meeting the above In the case of, the first adhesive may also have a variety of other structural forms, which are not listed here one by one.

[0082] Alternatively, in some embodiments, the structure of the block copolymer may be selected from or At least one of , wherein a and b are independently integers greater than 0.

[0083] In the block copolymer having the above structure, the monomer used to prepare the polyacrylic acid segment may be an acrylic acid monomer, and the monomer used to prepare the soft segment may be 2-methoxyethyl acrylate (EGMEA) or ethoxyethoxyethyl acrylate (EOEOEA).

[0084] In some specific embodiments, based on the total mass of the block copolymer, the mass proportion of the flexible segment is 2% to 10%. As an example, based on the total mass of the block copolymer, the mass proportion of the flexible segment can be any one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range between any two of them. By having the mass proportion of the flexible segment within the above range, the flexibility of the polymer can be effectively improved, the mechanical stress generated by the volume change of the negative electrode active material can be buffered, and the structural stability of the negative electrode active material can be ensured.

[0085] In some specific embodiments, the number average molecular weight of the block copolymer is 1000 to 100000. As an example, the number average molecular weight of the block copolymer can be any one of 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 50000, 100000 or any range between two thereof. By controlling the number average molecular weight of the block copolymer within the above range, the conductive binder can have good stretchability and elasticity, thereby making the negative electrode sheet have good capacity retention.

[0086] In this application, the term "number average molecular weight" refers to the average molecular weight of the number of molecules in a polymer as a statistical weight.

[0087] The conductive binder of the present application contains carbon material. Generally, carbon material is light in weight and has good conductivity, and is a pole piece conductive material with great application value. The above-mentioned carbon material coated with phenolic hydroxyl organic compound can be a carbon material surface coated with phenolic hydroxyl organic compound by non-covalent bond grafting to achieve modification of the carbon material. On the one hand, the phenolic hydroxyl organic compound contains a large amount of phenolic hydroxyl groups, which can inhibit the mutual agglomeration of carbon materials and improve the dispersibility of carbon materials in monomer solutions such as acrylic acid. On the other hand, the carbon material coated with phenolic hydroxyl organic compound can form a three-dimensional network structure with the block copolymer. By grafting and coating the phenolic hydroxyl organic compound on the surface of the carbon material, the compatibility of the carbon material and the block copolymer is improved, thereby reducing the separation of the two.

[0088] The carbon material coated with a phenolic hydroxyl organic compound includes a carbon material and a phenolic hydroxyl organic compound coating layer coated on the surface of the carbon material, that is, the carbon material coated with a phenolic hydroxyl organic compound can be a core-shell structure, the core layer (inner core) is a carbon material, the shell layer (outer shell) is a phenolic hydroxyl organic compound coating layer, and the carbon phenolic hydroxyl organic compound coating layer is coated on at least part of the outer surface of the carbon material.

[0089] It should be pointed out that in the present application, the "coating" is not limited to direct coating, but also includes indirect coating. For example, the carbon material coated with the phenolic hydroxyl organic compound may be that there is no other structure between the phenolic hydroxyl organic compound and the outer surface of the carbon material, or there may be one or more layers of other structures between the phenolic hydroxyl organic compound and the outer surface of the carbon material. Preferably, there is no other structure between the phenolic hydroxyl organic compound and the outer surface of the carbon material.

[0090] In the present application, the term "phenolic hydroxyl group" refers to Ar-OH, where Ar is an aromatic ring.

[0091] In some specific embodiments, the mass ratio of the block copolymer and the carbon material coated by the phenolic hydroxyl organic compound is 1:(0.02-0.05). As an example, the mass ratio of the block copolymer and the carbon material coated by the phenolic hydroxyl organic compound can be any point value of 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05 or any range value between two of them. By controlling the mass ratio of the block copolymer and the carbon material coated by the phenolic hydroxyl organic compound within the above range, while ensuring that the conductive binder has good stability, the negative electrode plate can also have excellent capacity retention.

[0092] In some specific embodiments, the block copolymer and the carbon material coated with the phenolic hydroxyl organic compound are blended to form a three-dimensional network structure. For example, in the process of mixing acrylic acid, acrylate organic matter containing ether radicals, carbon material coated with the phenolic hydroxyl organic compound, initiator and solvent for polymerization reaction, acrylic acid and acrylate organic matter containing ether radicals can be polymerized to form a block copolymer, and the block copolymer can be copolymerized and cross-linked with the phenolic hydroxyl organic compound such as tannic acid in the carbon material coated with the phenolic hydroxyl organic compound to form a three-dimensional network structure.

[0093] In some embodiments, the phenolic hydroxy organic compound includes, but is not limited to, tannic acid.

[0094] The CAS number of tannic acid is 1401-55-4, and the structural formula is It contains a large amount of phenolic hydroxyl groups, which are widely present in plants and are easily available.

[0095] In some embodiments, the carbon material includes, but is not limited to, at least one of carbon nanotubes or graphene.

[0096] Preferably, the carbon material is selected from carbon nanotubes.

[0097] In some embodiments, the carbon nanotubes include, but are not limited to, at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0098] Carbon nanotubes, also known as buckytubes, are one-dimensional quantum materials with a special structure (radial dimensions are in the nanometer range, axial dimensions are in the micrometer range, and both ends of the tube are basically sealed). The geometric structure of single-walled carbon nanotubes can be regarded as carbon nanotubes formed by curling a single layer of graphene. The geometric structure of multi-walled carbon nanotubes can be regarded as carbon nanotubes formed by curling two or more layers of graphene.

[0099] In some specific embodiments, the diameter of the carbon nanotube is 1nm to 10nm, and the length of the carbon nanotube is 5μm to 50μm. As an example, the diameter of the carbon nanotube can be any point value of 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm or any range value between two of them, and the length of the carbon nanotube can be any point value of 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any range value between two of them. By controlling the diameter and length of the carbon nanotube within the above range, the carbon nanotube has a high aspect ratio, and the conductive network can be effectively constructed and the continuity of the conductive network can be maintained.

[0100] Thus, based on the above settings, the conductive adhesive of the present invention can improve the flexibility of the adhesive by using the introduced flexible segments, and the physical cross-linking structure formed by the flexible segments and the polyacrylic acid segments through the intermolecular hydrogen bonding can reduce the irreversible slip of the polymer chain, and maintain the structural integrity of the silicon electrode during the cycle; moreover, the conductive adhesive uses the introduction of carbon materials such as carbon nanotubes (CNTs) to give the adhesive a certain conductivity, and the conductive adhesive can serve as a bridge for electronic connection between particles, promote the migration of charge carriers between silicon particles, and make the conductive network of the silicon electrode still maintain continuity after multiple cycles. Therefore, the conductive adhesive is applied to the negative electrode sheet, which can further improve the electrochemical cycle performance of the negative electrode sheet.

[0101] [Method for preparing conductive adhesive]

[0102] In some embodiments, the present application provides a method for preparing a conductive adhesive, the method comprising the following steps:

[0103] S10, performing a first mixing of the carbon material and water, adjusting the pH value, and then adding a phenolic hydroxyl organic compound for a second mixing to obtain a carbon material coated with the phenolic hydroxyl organic compound;

[0104] S20, mixing acrylic acid, an acrylate organic substance containing an ether group, a carbon material coated with a phenolic hydroxyl organic compound, an initiator and a solvent, and performing a polymerization reaction to obtain a conductive adhesive.

[0105] It should be understood that all the features and advantages described above for the “conductive adhesive” are also applicable to the “method for preparing the conductive adhesive” and will not be described in detail here.

[0106] In the present application, a carbon material is coated in a phenolic hydroxy organic compound, and then the carbon material coated with the phenolic hydroxy organic compound, acrylic acid, and an ether-oxygenated acrylate organic compound are mixed and polymerized to obtain a conductive binder. During the polymerization process, acrylic acid and an ether-oxygenated acrylate organic compound undergo free radical copolymerization, and finally an ether-oxygenated acrylate polymer is grafted onto the polyacrylic acid chain segment to form a block copolymer composed of a rigid chain segment and a flexible chain segment. At the same time, the carbon material coated with the phenolic hydroxy organic compound and the block copolymer form a physical three-dimensional network structure, which can effectively buffer the mechanical integrity and conductive network destruction caused by the volume change of the negative electrode active material during the charge and discharge process. That is, an acrylic ester organic substance with a flexible chain ether group is grafted into the rigid chain polyacrylic acid. The introduction of the flexible chain can improve the flexibility of the conductive binder, make it have better stretchability and elasticity, effectively buffer the mechanical stress generated by the volume change of the negative electrode active material during the charge and discharge process, and maintain the structural integrity of the negative electrode active material; the addition of carbon material can give the conductive binder a certain conductivity, and then can serve as a bridge for electronic connection between particles, promote the charge carrier migration of the negative electrode active material, and ensure the continuity of the conductive network during the cycle.

[0107] The phenolic hydroxy organic compound is coated on the surface of the carbon material through non-covalent bonding to avoid the agglomeration and sedimentation of the carbon material itself, so that it can be better dispersed in monomer solutions such as acrylic acid; at the same time, the carbon material coated with the phenolic hydroxy organic compound can form a physical cross-linked network with the block copolymer formed by monomer polymerization to reduce the separation of the two.

[0108] In some specific embodiments, the mass ratio of the carbon material to water is 1:(50-300). As an example, the mass ratio of the carbon material to water can be any one of 1:50, 1:100, 1:120, 1:150, 1:200, 1:250, 1:280, 1:300 or a range between any two of them.

[0109] In some specific embodiments, the first mixing time is 3 hours to 6 hours. As an example, the first mixing time can be any one of 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours, or a range between any two of them.

[0110] In some specific embodiments, the target pH value is 8 to 9; preferably, the target pH value is 8.3 to 8.8. As an example, the target pH value can be any point value among 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, or a range value between any two of them. By adjusting the pH value of the carbon material solution within the above range, conditions are provided for the subsequent coating of the carbon material with the ether group-containing acrylate organic matter. Under weakly alkaline conditions, the ether group-containing acrylate organic matter can be coated on the surface of the carbon material through non-covalent bond modification, thereby improving the stability of the carbon material coated with the ether group-containing acrylate organic matter.

[0111] In some specific embodiments, the pH value can be adjusted by adding a buffer, such as a Tris buffer.

[0112] In some specific embodiments, the mass ratio of the phenolic hydroxyl organic compound to the carbon material is (0.1-0.3):1. As an example, the mass ratio of the phenolic hydroxyl organic compound to the carbon material can be any point value of 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.22:1, 0.25:1, 0.28:1, 0.3:1, or a range value between any two of them. When the mass ratio of the phenolic hydroxyl organic compound to the carbon material is within the above range, the coating effect of the phenolic hydroxyl organic compound on the carbon material can be more effectively achieved, the agglomeration of the carbon material itself can be avoided, and the carbon material can be evenly dispersed in the subsequent monomer solution such as acrylic acid.

[0113] In some specific embodiments, the second mixing time is 2 hours to 5 hours. As an example, the second mixing time can be any one of 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, and 5 hours, or a range between any two of them.

[0114] Therefore, controlling the above process parameters within the given range is conducive to preparing high-quality carbon materials coated with phenolic hydroxyl organic compounds, which can further improve the performance of the conductive adhesive of the present application. Those skilled in the art can selectively adjust one or more of the above process parameters according to actual production conditions.

[0115] In the present application, step S10 mainly uses phenolic hydroxyl organic compounds such as tannic acid to perform non-covalent bond modification on the surface of carbon materials such as carbon nanotubes or graphene. In a neutral buffer solution, phenolic hydroxyl organic compounds such as tannic acid can stably coat the surface of carbon materials such as carbon nanotubes or graphene.

[0116] As an example, step S10, preparation of a carbon material coated with a phenolic hydroxyl organic compound, specifically includes:

[0117] Mix 1g of carbon material such as single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene with 100-300g of water for 3-6h, such as by ultrasonic dispersion; then adjust the pH value to 8-9, preferably 8.3-8.8, using a buffer solution such as Tris buffer, and then add 0.1-0.3g of phenolic hydroxyl organic compound such as tannic acid and mix for 2h-5h, such as by stirring at room temperature, and then filter and dry to obtain a carbon material coated with the phenolic hydroxyl organic compound.

[0118] Furthermore, the above step S20 mainly adds the copolymerized ether-containing acrylic acid ester organic matter and the carbon material coated with the phenolic hydroxy organic compound obtained in step S10 into the acrylic acid (AA) monomer, initiates free radical polymerization under the action of an initiator, and obtains a conductive adhesive.

[0119] In some specific embodiments, the structure of the acrylate organic compound containing an ether group is:

[0120]

[0121] Wherein, m and n are independently integers from 1 to 5; that is, m can be an integer of 1, 2, 3, 4 or 5, n can be an integer of 1, 2, 3, 4 or 5, and the values ​​of m and n can be the same or different.

[0122] Alternatively, in some specific embodiments, the acrylate organic compound containing an ether group may be at least one of 2-methoxyethyl acrylate (EGMEA) or ethoxyethoxyethyl acrylate (EOEOEA). That is, the structure of 2-methoxyethyl acrylate is The CAS number is 3121-61-7, and the structure of ethoxyethoxyethyl acrylate is The CAS number is 7328-17-8.

[0123] Of course, in meeting the above In the case of the structure, the ether-oxygen-containing acrylic ester organic matter can also have a variety of other structural forms, which are not listed here one by one.

[0124] In some specific embodiments, the mass ratio of acrylic acid to solvent is 1:(18-50), preferably 1:(20-50). As an example, the mass ratio of acrylic acid to solvent can be any one of 1:18, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50 or a range between any two of them.

[0125] In some specific embodiments, the mass ratio of acrylic acid to the acrylate organic compound containing an ether group is 1:(0.02-0.1). As an example, the mass ratio of acrylic acid to the acrylate organic compound containing an ether group can be any one of 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, or a range between any two of them.

[0126] In some specific embodiments, the mass ratio of acrylic acid to the carbon material coated with the phenolic hydroxyl organic compound is 1:(0.02-0.1). As an example, the mass ratio of acrylic acid to the carbon material coated with the phenolic hydroxyl organic compound can be any one of 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1 or a range between any two of them.

[0127] In some specific embodiments, the mass ratio of acrylic acid to initiator is 1:(0.1-0.2). As an example, the mass ratio of acrylic acid to initiator can be any one of 1:0.1, 1:0.12, 1:0.14, 1:0.15, 1:0.18, 1:0.2 or a range between any two of them.

[0128] In some specific embodiments, the polymerization reaction temperature is 60°C to 90°C, and the polymerization reaction time is 12h to 24h. As an example, the polymerization reaction temperature can be any one of 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or a range between any two thereof, and the polymerization reaction time can be any one of 12h, 14h, 16h, 18h, 20h, 22h, 24h, or a range between any two thereof.

[0129] In some specific embodiments, the polymerization reaction atmosphere is an inert atmosphere, such as nitrogen.

[0130] In some specific embodiments, the solvent includes, but is not limited to, any one of N,N-dimethylformamide, N-methyl-2-pyrrolidone, methanol or ethanol, or a combination of two or more in any proportion.

[0131] Preferably, the solvent is selected from N,N-dimethylformamide (DMF).

[0132] In some specific embodiments, the initiator includes, but is not limited to, any one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide, or a combination of two or more of them in any ratio.

[0133] Preferably, the initiator is selected from azobisisobutyronitrile (AIBN).

[0134] However, the present application is not limited to these solvents and initiators, and other solvents and initiators that can be used in polyacrylic acid modification can also be used in the present application. The above substances can be used alone or in combination of two or more.

[0135] In some specific embodiments, after the polymerization reaction is completed, post-treatment is further included to obtain a conductive adhesive; the post-treatment includes: placing the product obtained after the polymerization reaction in liquid nitrogen for quenching, then centrifuging, and then washing and freeze-drying.

[0136] Optionally, washing includes first washing with an alkane solvent and then washing with water; the alkane solvent may be n-hexane.

[0137] Optionally, the freeze drying temperature is -45°C to -55°C, and the freeze drying time is 12h to 24h. As an example, the freeze drying temperature can be any point value of -45°C, -46°C, -48°C, -50°C, -52°C, -55°C, or a range value between any two of them, and the freeze drying time can be any point value of 12h, 14h, 16h, 18h, 20h, 24h, or a range value between any two of them.

[0138] As an example, step S20 specifically includes:

[0139] Nitrogen is introduced into a container containing 20 to 50 g of a solvent, 1 g of acrylic acid, 0.02 to 0.1 g of an ether-containing acrylic ester organic matter, 0.02 to 0.1 g of a carbon material coated with a phenolic hydroxyl organic compound and 0.1 to 0.2 g of an initiator are added, stirred evenly, placed in an oil bath at 60 to 90° C. under nitrogen purge, and stirred for polymerization for 12 to 24 hours. After the polymerization reaction is completed, the resulting product is placed in liquid nitrogen for quenching, then centrifuged, washed with n-hexane and water, and finally freeze-dried at -45° C. to -55° C. for 12 to 24 hours to obtain a conductive adhesive.

[0140] [Negative electrode]

[0141] In some embodiments, the present application provides a negative electrode sheet, which includes a negative electrode active material and the above-mentioned conductive binder or the above-mentioned conductive binder prepared.

[0142] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, the negative electrode active layer contains a binder, and the binder includes the conductive binder of any of the above embodiments or the conductive binder obtained by the preparation method of any of the above embodiments.

[0143] In the present application, the negative electrode active layer is located on at least one side of the negative electrode current collector, and the negative electrode active material layer includes: negative electrode active material (also called negative electrode active material) and the conductive binder described above. Therefore, the negative electrode sheet has all the characteristics and advantages of the conductive binder described above, which will not be repeated here.

[0144] The negative electrode active layer is disposed on at least one surface of the negative electrode current collector along the thickness direction, which means that the negative electrode active layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. The "surface" here can be the entire area of ​​the current collector or a partial area of ​​the current collector. This application has no special restrictions on this, as long as the purpose of this application can be achieved.

[0145] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode active layer is disposed on the two opposite surfaces of the negative electrode current collector. It is understood that in other embodiments, the negative electrode active layer can also be stacked on any one of the two surfaces of the negative electrode current collector.

[0146] In some embodiments, in the negative electrode sheet, the negative electrode current collector may be a metal foil or a composite current collector. As an example, the negative electrode current collector may be a metal material such as copper, copper alloy, aluminum, aluminum alloy, nickel, stainless steel, nickel-plated steel, etc. In addition, the current collector may be used in various forms, such as a film, a sheet, a foil, a mesh, a porous body, a foam, and a non-woven fabric.

[0147] In some specific embodiments, the mass of the conductive binder is 2% to 5% of the negative electrode active material. As an example, the mass of the conductive binder can be any one of 2%, 2.5%, 3%, 4%, 4.5%, 5% of the negative electrode active material or a range of any two thereof.

[0148] In some specific embodiments, the negative electrode active material includes a silicon-carbon composite material. Optionally, the silicon-carbon composite material can be a conventional commercially available material. However, the present application is not limited to these negative electrode active materials, and other materials that can be used as negative electrode active materials can also be used in the present application. The above-mentioned materials can be used alone or in combination of two or more.

[0149] Optionally, the negative electrode active layer may further include a conductive agent. That is, the negative electrode active layer may include a negative electrode active material, the above-mentioned conductive binder and an optional conductive agent. The present application has no particular restrictions on the type of conductive agent in the negative electrode sheet, and any conductive agent known in the art may be used.

[0150] In some specific embodiments, the surface density of the negative electrode sheet is 7 to 15 mg / cm 2As an example, the surface density of the negative electrode sheet can be 7 mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 , 12mg / cm 2 、15mg / cm 2 When the surface density of the negative electrode sheet is within the above range, the rate discharge performance of the battery and the safety of the battery can be improved.

[0151] [Battery]

[0152] In some embodiments, the present application provides a battery, comprising the conductive adhesive as claimed in claim 1, the conductive adhesive prepared by the method as described above, or the negative electrode sheet as described above.

[0153] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may be a battery cell, or the battery may include a battery module (or battery module) or a battery pack, etc.

[0154] The battery includes the aforementioned negative electrode sheet, and thus has all the features and advantages of the aforementioned conductive adhesive and negative electrode sheet, which will not be described in detail here.

[0155] In some embodiments, the battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The electrode assembly can be a wound structure or a laminated structure, which is not limited in the embodiments of the present application.

[0156] In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module.

[0157] In some embodiments, the battery may be a battery pack, which may include a case and battery cells, wherein the battery cells or battery modules are accommodated in the case.

[0158] It should be understood that multiple battery cells can be assembled into a battery module or a battery pack. The number of battery cells contained in a battery module or a battery pack can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module or battery pack.

[0159] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0160] In the embodiments of the present application, the preparation method of the battery cell or the battery is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a battery cell is obtained. Optionally, multiple battery cells can be further connected in series or in parallel or in a mixed connection to form a battery module. Optionally, multiple battery modules can also be connected in series or in parallel or in a mixed connection to form a battery pack. Optionally, in some embodiments, multiple battery cells can also directly form a battery pack.

[0161] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0162] Example 1

[0163] The preparation of the conductive adhesive comprises the following steps:

[0164] S10. Disperse 3 g of carbon nanotubes (with a tube diameter of 5 nm and a length of 25 μm) in 150 mL of deionized water, perform ultrasonic dispersion treatment for 6 h, add Tris buffer solution to adjust the pH to 8.7; then add 0.5 g of tannic acid (TA), stir at room temperature for 3 h, and then filter and dry to obtain carbon nanotubes coated with tannic acid.

[0165] S20. Nitrogen was introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, and 5 g of acrylic acid (AA), 0.1 g of 2-methoxyethyl 2-acrylate (EGMEA), 0.1 g of carbon nanotubes coated with tannic acid and 0.5 g of azobisisobutyronitrile (AIBN) were added and stirred evenly; the mixture was placed in an oil bath at 80° C. under nitrogen purge and stirred for polymerization reaction for 15 h. After the polymerization reaction, the product was placed in liquid nitrogen for quenching, and then centrifuged, and then washed with n-hexane and water in turn, and finally freeze-dried at -45° C. for 24 h to obtain a conductive adhesive.

[0166] Example 2

[0167] The preparation of the conductive adhesive comprises the following steps:

[0168] S10. Disperse 3 g of carbon nanotubes (with a tube diameter of 2 nm and a length of 10 μm) in 600 mL of deionized water, perform ultrasonic dispersion treatment for 4 h, add Tris buffer solution to adjust the pH to 8.5; then add 0.3 g of tannic acid (TA), stir at room temperature for 3 h, filter and dry, and obtain carbon nanotubes coated with tannic acid.

[0169] S20. Nitrogen was introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, and 5 g of acrylic acid (AA), 0.1 g of ethoxyethoxyethyl acrylate (EOEOEA), 0.1 g of carbon nanotubes coated with tannic acid and 0.5 g of azobisisobutyronitrile (AIBN) were added and stirred evenly; the mixture was placed in an oil bath at 80°C under nitrogen purge and stirred for polymerization for 15 h. After the polymerization reaction, the product was placed in liquid nitrogen for quenching, and then centrifuged, and then washed with n-hexane and water in turn, and finally freeze-dried at -45°C for 24 h to obtain a conductive adhesive.

[0170] Example 3

[0171] The preparation of the conductive adhesive comprises the following steps:

[0172] S10. Disperse 3 g of carbon nanotubes (with a tube diameter of 5 nm and a length of 25 μm) in 600 mL of deionized water, perform ultrasonic dispersion treatment for 4 h, add Tris buffer solution to adjust the pH to 8.7; then add 0.3 g of tannic acid (TA), stir at room temperature for 5 h, filter and dry, and obtain carbon nanotubes coated with tannic acid.

[0173] S20. Nitrogen is introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, and 3 g of acrylic acid (AA), 0.25 g of ethoxyethoxyethyl acrylate (EOEOEA), 0.1 g of carbon nanotubes coated with tannic acid and 0.6 g of azobisisobutyronitrile (AIBN) are added and stirred evenly; the mixture is placed in an oil bath at 70°C under nitrogen purge and stirred for polymerization for 24 hours. After the polymerization reaction, the product is placed in liquid nitrogen for quenching, and then centrifuged, and then washed with n-hexane and water in turn, and finally freeze-dried at -45°C for 24 hours to obtain a conductive adhesive.

[0174] Example 4

[0175] The preparation method of the conductive adhesive is similar to that of Example 1, except that:

[0176] In step S10, the carbon nanotubes are replaced with graphene.

[0177] The rest are the same as in Example 1.

[0178] Example 5

[0179] The preparation method of the conductive adhesive is similar to that of Example 1, except that:

[0180] In step S10, 0.6 g of tannic acid (TA) is added.

[0181] The rest are the same as in Example 1.

[0182] Example 6

[0183] The preparation method of the conductive adhesive is similar to that of Example 1, except that:

[0184] In step S10, 0.9 g of tannic acid (TA) was added.

[0185] The rest are the same as in Example 1.

[0186] Example 7

[0187] The preparation method of the conductive adhesive is similar to that of Example 1, except that:

[0188] In step S20, 3 g of acrylic acid (AA), 0.25 g of 2-methoxyethyl 2-acrylate, 0.1 g of carbon nanotubes coated with tannic acid, and 0.6 g of azobisisobutyronitrile (AIBN) were added.

[0189] The rest are the same as in Example 1.

[0190] Example 8

[0191] The preparation method of the conductive adhesive is similar to that of Example 1, except that:

[0192] In step S20, 3 g of acrylic acid (AA), 0.15 g of ethoxyethoxyethyl acrylate (EOEOEA), 0.1 g of carbon nanotubes coated with tannic acid, and 0.6 g of azobisisobutyronitrile (AIBN) were added.

[0193] The rest are the same as in Example 1.

[0194] Example 9

[0195] The preparation method of the binder is similar to that of Example 1, except that:

[0196] In step S20, 0.06 g of carbon nanotubes coated with tannic acid are added.

[0197] The rest are the same as in Example 1.

[0198] Example 10

[0199] The preparation method of the binder is similar to that of Example 1, except that:

[0200] In step S20, 0.08 g of carbon nanotubes coated with tannic acid are added.

[0201] The rest are the same as in Example 1.

[0202] Comparative Example 1 (no addition of carbon nanotubes coated with tannic acid)

[0203] The preparation of the conductive adhesive comprises the following steps:

[0204] Nitrogen was introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, and 5 g of acrylic acid (AA), 0.1 g of 2-methoxyethyl 2-acrylate (EGMEA) and 0.5 g of azobisisobutyronitrile (AIBN) were added and stirred evenly; the mixture was placed in an 80°C oil bath under nitrogen purge and stirred for polymerization for 15 hours. After the polymerization reaction, the obtained product was placed in liquid nitrogen for quenching, then centrifuged, washed with n-hexane and water in turn, and finally freeze-dried at -45°C for 24 hours to obtain a conductive adhesive.

[0205] Comparative Example 2 (without adding comonomer EOEOEA)

[0206] The preparation of the conductive adhesive comprises the following steps:

[0207] S10. Disperse 3 g of carbon nanotubes (with a tube diameter of 5 nm and a length of 25 μm) in 600 mL of deionized water, perform ultrasonic dispersion treatment for 4 h, add Tris buffer solution to adjust the pH to 8.5; then add 0.3 g of tannic acid (TA), stir at room temperature for 3 h, filter and dry, to obtain carbon nanotubes coated with tannic acid.

[0208] S20. Nitrogen was introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, and 5 g of acrylic acid (AA), 0.1 g of carbon nanotubes coated with tannic acid and 0.5 g of azobisisobutyronitrile (AIBN) were added and stirred evenly; the mixture was placed in an oil bath at 80°C under nitrogen purge and stirred for polymerization for 15 h. After the polymerization reaction, the obtained product was placed in liquid nitrogen for quenching, and then centrifuged, and then washed with n-hexane and water in turn, and finally freeze-dried at -45°C for 24 h to obtain a conductive adhesive.

[0209] Comparative Example 3 (no addition of carbon nanotubes coated with tannic acid and comonomer EOEOEA)

[0210] The preparation of the conductive adhesive comprises the following steps:

[0211] Nitrogen was introduced into a container containing 100 mL of N,N-dimethylformamide (DMF) solution, 5 g of acrylic acid (AA) and 0.5 g of azobisisobutyronitrile (AIBN) were added and stirred evenly; the mixture was placed in an 80°C oil bath under nitrogen purge and stirred for polymerization for 15 hours. After the polymerization reaction, the obtained product was placed in liquid nitrogen for quenching, then centrifuged, washed with hexane and water in turn, and finally freeze-dried at -45°C for 24 hours to obtain a conductive adhesive.

[0212] The conductive adhesive prepared in the above examples and comparative examples is applied to a battery to prepare the battery. The preparation of the battery includes:

[0213] 1. Preparation of silicon negative electrode sheet, including:

[0214] The prepared conductive adhesive is dissolved in deionized water to obtain a 5% glue solution;

[0215] The commercially available silicon-carbon negative electrode and the conductive agent conductive carbon black Super P were ground evenly in a mortar, and then the glue was added and ground for 30 minutes, and water was added to adjust the viscosity to 3500mPa·s to obtain a slurry; in the slurry, the mass ratio of the negative electrode active material, the conductive agent and the conductive binder was 8:1:1;

[0216] The slurry was evenly coated on the negative electrode current collector copper foil by a coating machine, and after vacuum drying at 90° C. for 24 h, the thickness of the coating on the copper foil after drying was 45 μm; the negative electrode sheet was obtained by cutting into discs with a diameter of 12 mm.

[0217] 2. A button cell was assembled using a lithium sheet as the counter electrode and the prepared silicon negative electrode as the working electrode. The diaphragm used a commercial three-layer PP / PE / PP diaphragm, the electrolyte used was 1 M LiPF6 (EC:DMC:EMC=1:1:1, V / V / V), and 5 wt% of fluoroethylene carbonate (FEC) was added as an electrolyte additive.

[0218] Performance Testing

[0219] After the battery is assembled, it is left to stand for 12 hours for electrochemical performance testing, which specifically includes the following steps:

[0220] The constant current charge and discharge cycle and rate performance test were carried out at room temperature on the Blue Electric charge and discharge tester, with a voltage window of 0.005V to 1.5V. Before the test, the battery was cycled 3 times at a rate of 0.1C for low current activation.

[0221] (1) Capacity retention rate after 100 cycles: At 25°C, discharge the battery at 0.5C constant current to 0.005V and let it stand for 5 min; then charge it at 0.5C constant current to 1.5V and let it stand for 5 min, and repeat this cycle for 100 cycles; record the charging capacity of the first cycle as the initial capacity, then the capacity retention rate of the 100th cycle = charging capacity of the 100th cycle / charging capacity of the first cycle * 100%.

[0222] (2) Full-charge expansion rate of the electrode: During the above-mentioned 100-cycle capacity retention test, the initial electrode thickness and the thickness of the electrode after the second charge are recorded. Then, the full-charge expansion rate of the electrode = (thickness of the electrode after the second charge - thickness of the initial electrode) / thickness of the initial electrode * 100%.

[0223] (3) 1C / 0.1C capacity retention rate: maintain a discharge rate of 0.1C, and charge rates from 0.1C, 0.2C, 0.5C to 1C, with 5 cycles at each rate. Then, the 1C / 0.1C capacity retention rate = average charge capacity of 5 cycles at 1C / average charge capacity of 5 cycles at 0.1C.

[0224] The test results are shown in Table 1.

[0225] Table 1 Electrochemical performance test results of batteries in various embodiments and comparative examples

[0226]

[0227]

[0228] As can be seen from Table 1, compared with Comparative Examples 1-3, the battery prepared by the conductive binder provided in Examples 1-10 of the present invention has a better capacity retention rate during the charge and discharge process, and improves the cycle performance and rate performance of the battery. Moreover, compared with Comparative Examples 1-3, the pole piece prepared by the conductive binder provided in Examples 1-10 of the present invention has a reduced expansion rate during the charge and discharge process, indicating that the conductive binder provided by the present invention can effectively buffer the mechanical stress generated by the volume change of the negative electrode active material during the charge and discharge process, maintain the structural integrity of the negative electrode active material during the charge and discharge cycle, and thus alleviate the expansion of the pole piece.

[0229] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0230] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0231] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0232] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0233] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A conductive adhesive, characterized in that: It includes a block copolymer and a carbon material coated with a phenolic hydroxyl organic compound; The block copolymer comprises a polyacrylic acid segment and a soft segment; The soft segment comprises an acrylic polymer containing an ether group.

2. The conductive adhesive according to claim 1, characterized in that: Based on the total mass of the block copolymer, the mass proportion of the flexible segment is 2% to 10%; and / or, the mass ratio of the block copolymer to the carbon material coated with the phenolic hydroxyl organic compound is 1:(0.02-0.05); Preferably, the block copolymer and the carbon material coated with the phenolic hydroxyl organic compound are blended to form a three-dimensional network structure.

3. The conductive adhesive according to claim 1, characterized in that: The phenolic hydroxy organic compound includes tannic acid; The carbon material includes at least one of carbon nanotubes or graphene; Preferably, the carbon nanotubes include at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes; Preferably, the diameter of the carbon nanotube is 1 nm to 10 nm, and the length of the carbon nanotube is 5 μm to 50 μm.

4. The conductive adhesive according to any one of claims 1 to 3, characterized in that: The number average molecular weight of the block copolymer is 1000 to 100000; The structural formula of the acrylic acid ester polymer containing ether radical is as follows: Wherein, m and n are independently integers from 1 to 5, and b is an integer greater than 0; Preferably, the structural formula of the acrylic polymer containing ether radicals is selected from or At least one of .

5. A method for preparing a conductive adhesive, characterized in that: The following steps are involved: The carbon material and water are first mixed, the pH value is adjusted, and then a phenolic hydroxyl organic compound is added for second mixing to obtain a carbon material coated with the phenolic hydroxyl organic compound; Acrylic acid, acrylate organic matter containing ether radical, carbon material coated with phenolic hydroxyl organic compound, initiator and solvent are mixed and polymerized to obtain conductive adhesive.

6. The method for preparing a conductive adhesive according to claim 5, characterized in that: The mass ratio of the carbon material to water is 1:(50-300); And / or, the target pH value is 8 to 9; And / or, the mass ratio of the phenolic hydroxyl organic compound to the carbon material is (0.1-0.3):1; And / or, the first mixing time is 3h to 6h; And / or, the second mixing time is 2h to 5h.

7. The method for preparing a conductive adhesive according to claim 5, characterized in that: The preparation method satisfies at least one of the following (1) to (8): (1) The structure of the ether-oxygen-containing acrylic acid ester organic compound is: Wherein, m and n are independently integers from 1 to 5; Preferably, the ether-oxygen-containing acrylic acid ester organic compound includes at least one of 2-methoxyethyl acrylate or ethoxyethoxyethyl acrylate; (2) The mass ratio of the acrylic acid to the solvent is 1:(18-50); (3) The solvent includes at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone, methanol or ethanol; (4) The mass ratio of the acrylic acid to the ether-oxy group-containing acrylic ester organic matter is 1:(0.02-0.1); (5) The mass ratio of the acrylic acid to the carbon material coated with the phenolic hydroxyl organic compound is 1:(0.02-0.1); (6) The mass ratio of the acrylic acid to the initiator is 1:(0.1-0.2); (7) The initiator comprises at least one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide; (8) The polymerization reaction temperature is 60° C. to 90° C., and the polymerization reaction time is 12 h to 24 h.

8. The method for preparing a conductive adhesive according to any one of claims 5 to 7, characterized in that: After the polymerization reaction is completed, post-processing is also included to obtain a conductive adhesive; The post-treatment comprises: placing the product obtained after the polymerization reaction in liquid nitrogen for quenching, then centrifuging, and then washing and freeze-drying; Preferably, the freeze-drying temperature is -45°C to -55°C, and the freeze-drying time is 12h to 24h.

9. A negative electrode sheet, characterized in that: Comprising a negative electrode active material and a conductive binder as claimed in any one of claims 1 to 4 or a conductive binder prepared by the method as claimed in any one of claims 5 to 8; Preferably, the mass of the conductive binder is 2% to 5% of the negative electrode active material; Preferably, the negative electrode active material comprises a silicon-carbon composite material; Preferably, the surface density of the negative electrode sheet is 7 to 15 mg / cm 2 .

10. A battery, characterized in that: The conductive adhesive comprises the conductive adhesive as claimed in any one of claims 1 to 4, or the conductive adhesive prepared by the method as claimed in any one of claims 5 to 8, or the negative electrode sheet as claimed in claim 9.